The Relationship between Uterine Leiomyoma with Premature Rupture of Membranes in Pregnant Women - Maryam Razavi; Farzaneh Rashidi Fakari; Aref Rigi; Farahnaz Farzaneh (Mashhad University of Medical Sciences, 2019)
Introduction: Uterine leiomyoma is the most prevalent benign uterine tumor in women which develop in nearly 20-40% of women of reproductive age. Pregnancy in women with uterine leiomyoma is considered as a high-risk pregnancy that lead to many complications. This study was performed with aim to investigate the relationship of uterine leiomyoma with premature rupture of membranes in pregnant women. Methods: This descriptive-analytical study was conducted on 500 pregnant women referred to Ali-ibn Abi Talib Hospital in Zahedan from April 2015 to March2017. The qualified pregnant women were divided into two groups of leiomyoma and non-leiomyoma, based on the presence of uterine lymphoma diagnosed in early pregnancy ultrasound. Two groups were examined for number, size and location of leiomyoma. Data were analyzed using SPSS software (version 21), descriptive and Chi-square tests. P Results: Among 500 pregnant women who were included in the study, 18.6% (N=93) had uterine lymphoma and 81.4% (N=407) were without uterine leiomyoma. The prevalence of premature rupture of the membrane in the uterine leiomyoma group was 25.85% (N=24) and 9.33% (N=38) in without uterine leiomyoma group. There was significant relationship between premature rupture of membranes with the number and location of uterine lymphoma in pregnant women (p <0.001). Conclusion: There was significant relationship between premature rupture of membranes with uterine leiomyoma (number, size and location). Premature rupture of membranes was more prevalent in intramural mayoma and in mayoma with diameter more than 5 cm.